2007
DOI: 10.2139/ssrn.1194968
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Trade of Cultural Goods

Abstract: International trade flows of cultural goods have grown rapidly over the last decades and their liberalization will be an important issue of future multilateral trade negotiations. In this paper, we focus on bilateral trade in cultural goods and investigate its determinants. Furthermore, we use trade in cultural goods as a proxy for countries' cultural proximity and study if countries with proximate cultural tastes have more intense bilateral exchanges. Our estimations show a positive and significant influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 47 publications
(25 reference statements)
2
47
0
Order By: Relevance
“…That is, if two countries become culturally closer, the tourism trade between these two countries can be expected to flourish. The results are smaller for total trade, with a coefficient of 0.1, which is comparable to the results from Disdier et al (2010), who find the cultural preferences variable close to 0.2. In this study, it is concluded that the effect of cultural preferences is almost 4 times larger on international tourism exports than on total exports.…”
Section: Estimation Resultssupporting
confidence: 47%
See 3 more Smart Citations
“…That is, if two countries become culturally closer, the tourism trade between these two countries can be expected to flourish. The results are smaller for total trade, with a coefficient of 0.1, which is comparable to the results from Disdier et al (2010), who find the cultural preferences variable close to 0.2. In this study, it is concluded that the effect of cultural preferences is almost 4 times larger on international tourism exports than on total exports.…”
Section: Estimation Resultssupporting
confidence: 47%
“…However, culture itself is an item of consumption, and the volume/value of bilateral trade in cultural products reveals consumer preferences. Disdier et al (2010) propose that the volume of trade in cultural products can be used to determine the level of cultural preferences between two trading partners.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kluver and Fu (2004) note that transmission of cultural values is closely related to sharing cultural goods and services such as movies, TV series, music and other works of art across borders. Disdier et al (2010) use bilateral trade in cultural goods as a proxy for countries' cultural proximity. Hellmanzik and Schmitz (2015) use trade in audio-visual services based on bilateral hyperlinks and bilateral website visits as a proxy for cultural proximity.…”
Section: Dimensions Of Globalization: Economic Social and Political mentioning
confidence: 99%